HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN PEMERIKSAAN ANTENATAL CARE (ANC) PADA MASA PANDEMI COVID-19 DI PUSKESMAS RIJALI KOTA AMBON - Nova Bugis; Siti Nurhidayati; Aprisal Penuwel Hulakala (STIKES Pasapua Ambon, 2022)
Introduction: ANC services will prepare prospective mothers so that they are truly ready for pregnancy, childbirth and maintaining the environment so that the surrounding environment is able to protect the baby from infection. The current conditions set by the World Health Organization since early March 2020, as a pandemic caused by the Coronavirus Disease- 2019, known as the Covid-19 pandemic, had an impact on various public service sectors, especially the health sector. Problems that arise such as the amount of information that is not necessarily correct related to Covid-19 is spread in the community, there is still a wide variety of public understanding of Covid-19 and the level of public anxiety, especially pregnant women, is quite high and the level of public compliance with protocol provisions which is still low indirectly contributes to regularity ANC visits, (Ministry of Health Republic of Indonesia, 2020). To get optimal results from ANC visits, mothers should make regular ANC visits. According to WHO in 2016 it is better to make ANC visits 8 times from the previous 4 visits during pregnancy. Method: The design of this study used a cross-sectional approach to study the correlation dynamics of pregnant women’s knowledge about Antenatal Care (ANC) examinations during the Covid-19 pandemic in the Work Area of the Rijali Health Center. by way of approach and data collection that emphasizes the time of measurement at one time (point time approach). Results: From the results of this study it was stated that of the 40 respondents, it was found that the majority of pregnant women had poor knowledge, namely 24 people (60%), while pregnant women who had good knowledge were only 16 pregnant women (40%). This is caused by the education of pregnant women mostly in high school education, namely as many as 24 people (60%). As for the Antenatal Care Examination (ANC), most of the pregnant women who did not regularly carry out examinations were as many as 24 people (60%), and only 16 pregnant women who regularly carried out examinations (40%).